2022
DOI: 10.1111/irv.12954
|View full text |Cite
|
Sign up to set email alerts
|

Homologous PB1 gene promotes the replication efficiency of avian influenza H7N4 candidate vaccine virus

Abstract: Background The first and only case of human infection with the avian influenza A (H7N4) virus in China emerged in 2018. The H7N4 virus was distinct from previous H7N9 viruses and raised public concerns. Therefore, developing a suitable H7N4 candidate vaccine virus (CVV) remains crucial for potential pandemic preparedness. Methods We constructed a reassortant virus with a (6 + 2) genome composition, then introduced the polymerase basic protein 1 (PB1) from a wild‐type virus to develop a (5 + 3) reassortant viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…The M vRNA segment almost always originates from PR8 [ 10 , 16 , 17 ] and has been shown to confer a higher yield [ 11 ]. Analysis of 5:3 reassortants has revealed that the PB1 vRNA segment is frequently derived from the circulating virus [ 10 , 16 , 17 ] by conferring a higher yield [ 18 , 19 , 20 , 21 ]. Thus, the high yield of a candidate vaccine virus is often conferred by the PR8 M vRNA segment and the PB1 vRNA segment of the circulating virus.…”
Section: Discussionmentioning
confidence: 99%
“…The M vRNA segment almost always originates from PR8 [ 10 , 16 , 17 ] and has been shown to confer a higher yield [ 11 ]. Analysis of 5:3 reassortants has revealed that the PB1 vRNA segment is frequently derived from the circulating virus [ 10 , 16 , 17 ] by conferring a higher yield [ 18 , 19 , 20 , 21 ]. Thus, the high yield of a candidate vaccine virus is often conferred by the PR8 M vRNA segment and the PB1 vRNA segment of the circulating virus.…”
Section: Discussionmentioning
confidence: 99%